“Trites” Kajian Etnokuliner Etnik Batak Karo Di Desa Jaranguda Kecamatan Merdeka - Isnainy Fazryn; Nuriza Dora (Badan Penerbit STIEPARI Press, 2024)
The Batak tribe, which is divided into several tribes, is the majority of the population originating in North Sumatra Province. Including the Karo tribe, most of whom live in the Karo Highlands. The Batak people still carry out and maintain their ancestral cultural traditions. In Karo tribal ceremonies, food is a very important part. There are several types of food that are only available at traditional ceremonies. Typical Karo cuisine is unique in terms of the use of ingredients, it could even be said to be extreme. One of them is trites or grass found in the cow's stomach. Trites has qualified as a culinary tourist attraction, but it tastes strange and the method of making it is quite complicated. This is the problem in this research. The aim of this research is to find out how to make this trites food. This scientific writing uses ualitative methods with observation techniues carried out in local communities. To find out how to make trites food. Hedonic test results: taste, appearance and texture are acceptable. However, aromas that are too strong are less desirable. The result of the research show that Trites food is a food that is less popular, unlike other foods such as cimpa or tasak telu.